The mortality rate of electroconvulsive therapy: a systematic review and pooled analysis. (23rd March 2017) - Tørring, N.; Sanghani, S. N.; Petrides, G.; Kellner, C. H.; Østergaard, S. D.
Abstract : Objective: Electroconvulsive therapy (ECT) remains underutilized because of fears of cognitive and medical risks, including the risk of death. In this study, we aimed to assess the mortality rate of ECT by means of a systematic review and pooled analysis. Method: The study was conducted in adherence with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guideline. The ECT‐related mortality rate was calculated as the total number of ECT‐related deaths reported in the included studies divided by the total number of ECT treatments. Results: Fifteen studies with data from 32 countries reporting on a total of 766 180 ECT treatments met the inclusion criteria. Sixteen cases of ECT‐related death were reported in the included studies yielding an ECT‐related mortality rate of 2.1 per 100 000 treatments (95% CI: 1.2–3.4). In the nine studies that were published after 2001 (covering 414 747 treatments), there was only one reported ECT‐related death. Conclusion: The ECT‐related mortality rate was estimated at 2.1 per 100 000 treatments. In comparison, a recent analysis of the mortality of general anesthesia in relation to surgical procedures reported a mortality rate of 3.4 per 100 000. Our findings document that death caused by ECT is an extremely rare event.